Comparative toxicity and biodistribution assessments in rats following subchronic oral exposure to copper nanoparticles and microparticles. Issue 1 (December 2016) - Lee, In-Chul; Ko, Je-Won; Park, Sung-Hyeuk; Shin, Na-Rae; Shin, In-Sik; Moon, Changjong; Kim, Je-Hein; Kim, Hyoung-Chin; Kim, Jong-Choon
Abstract Background Copper nanoparticles (Cu NPs) have great potential in electronics and biomedical fields because of their efficient thermodynamic and anti-microbial properties. However, their potential toxic effects and kinetic data following repeated exposure are still unclear. Methods We evaluated the physicochemical properties of Cu NPs (25 nm) and copper microparticles (Cu MPs, 14–25 μm). Comparative in vivo toxicity of Cu NPs and Cu MPs was evaluated by conducting a 28-day repeated oral dose study at equivalent dose levels of 0, 100, 200, and 400 mg/kg/day (vehicle, 1 % hydroxypropyl methylcellulose). We determined Cu levels in the blood, tissues, urine, and feces by using inductively coupled plasma mass spectrometry. Results The solubility of Cu NPs and Cu MPs was 84.5 and 17.2 %, respectively, in an acidic milieu; however, they scarcely dissolved in vehicle or intestinal milieus. The specific surface area of Cu NPs and Cu MPs was determined to be 14.7 and 0.16 m2 /g, respectively. Cu NPs exhibited a dose-dependent increase of Cu content in the blood and tested organs, with particularly high levels of Cu in the liver, kidney, and spleen. Only for liver and kidney increased Cu levels were found in Cu MPs-treated rats. Cu NPs caused a dose-related increase in Cu levels in urine, whereas Cu MPs did not affect the urine Cu levels. Extremely high levels of Cu were detected in the feces of Cu MPs-treated rats, whereas much lower levels were detected in the feces of Cu NPs-treated rats. A comparative in vivo toxicity study showed that Cu NPs caused damages to red blood cells, thymus, spleen, liver, and kidney at ≥200 mg/kg/days, but Cu MPs did not cause any adverse effects even at the highest dose. Conclusions Overall, the in vivo repeated dose toxicity study of Cu NPs and Cu MPs demonstrated that large surface area and high solubility in physiological milieus could directly influence the toxicological responses and biodistribution of Cu particles when administered orally. Under these experimental conditions, the no-observed-adverse-effect levels of Cu NPs and Cu MPs were determined to be 100 and ≥400 mg/kg/day, respectively.